USING RFID TECHNOLOGY TO LOCATE MISSING BOOKS IN THE LIBRARY: A FEASIBILITY STUDY - Samani, Karan Kishorkumar (2006)
This dissertation aims to develop a Radio Frequency Identification (RFID) book tracking system that alerts a computer program for library use that a book has been placed on the wrong shelf and to test the large scale feasibility of it.